Activation of retinoid X receptors induces apoptosis in HL-60 cell lines. - Nagy, L (1995)
Retinoids induce myeloblastic leukemia (HL-60) cells to differentiate into granulocytes, which subsequently die by apoptosis. Retinoid action is mediated through at least two classes of nuclear receptors: retinoic acid receptors, which bind both all-trans retinoic acid and 9-cis retinoic acid, and retinoid X receptors, which bind only 9-cis retinoic acid. Using receptor-selective synthetic retinoids and HL-60 cell sublines with different retinoid responsiveness, we have investigated the contribution that each class of receptors makes to the processes of cellular differentiation and death. Our results demonstrate that ligand activation of retinoic acid receptors is sufficient to induce differentiation, whereas ligand activation of retinoid X receptors is essential for the induction of apoptosis in HL-60 cell lines.